The efficacy of Botulinum Toxin A on improving ease of care in the upper and lower limbs: A systematic review and meta-analysis using the Grades of Recommendation, Assessment, Development and Evaluation approach - Baker, J.; Pereira, Gavin (SAGE Publications Ltd, 2015)
OBJECTIVES: A systematic review and meta-analysis using the Grades of Recommendation, Assessment, Development and Evaluation (GRADE) approach; evaluating Botulinum Toxin type A efficacy on improving ease of care in the upper/lower limb. DATA SOURCES: Pubmed, Cinahl, Amed, Embase and Cochrane databases. English Language. Search to July 2014. REVIEW METHODS: All randomized, placebo controlled trials on adults with difficulty in caring for the upper/lower limb resulting from spasticity of any origin and treated with a single dose of Botulinum Toxin A. Evidence quality was assessed by GRADE. RESULTS: A total of 32 studies were reviewed. Meta-analysis was carried out on 11 upper limb and three lower limb studies. Evidence quality for the upper limb was moderate. A significant result for Botulinum Toxin A was found at four to 12 weeks for the upper limb (SMD 0.80, CI 0.55, 1.06, p < 0.0001). The effects were maintained for up to six months (SMD 0.48, CI 0.34, 0.62, p < 0.0001). Evidence quality was very low for the lower limb. Meta-analysis was only possible for global assessment of benefit. No significant effect was found. (PATIENT: RR 1.37 CI (0.94, 2.00) p = 0.11; clinician: RR 1.06 (0.84, 1.34) p = 0.60.) CONCLUSION: Botulinum Toxin A improves ease of care in the upper limb for up to six months. No conclusion can be drawn for the lower limb.